Adaptive potential of rhizoctonia solani AG-1 IA populations associated with rice and urochloa brizantha for thermal stress - Ramos-Molina, Lina Maria [UNESP]; Ceresini, Paulo Cezar [UNESP]; Vicentini, Samara Nunes Campos [UNESP]; Pereira, Danilo Augusto dos Santos [UNESP]; Conceição, Grace Ingrid [UNESP]; Silva-Herrera, María del Rosario; dos Santos, Pedro César [UNESP] (FapUNIFESP (SciELO), 2019)
A large number of widely distributed plant pathogens such as the phytopathogenic fungi of the genus Rhizoctonia are subject to extreme temperature fluctuations in their habitats. To survive such thermal fluctuations, these organisms have developed the capability of regulating their phenotypic values for specific thermal adaptations and to other specific environmental variations. The objective of this study was to determine the effects of thermal stress on the evolvability for mycelial growth in two host-distinct populations of Rhizoctonia solani AG-1 IA infecting either rice (OS6) or Urochloa (BBT1), and to compare them with a population of R. oryzae-sativae from rice (OS5), a species adapted to higher temperatures. The populations were subjected to two growth temperatures: 25°C and 35°C (optimal and stress temperatures for R. solani AG-1 IA). Based on mycelial growth, estimates of genotypic variance (IG), environmental variance (IE) and broad sense heritability (h2) were determined as measures of evolvability. The population OS5 of R. oryzae-sativae was almost not influenced by temperature stress, while at 35°C there was a reduction in h2 for the populations BBT1 and OS6 of R. solani AG-1 IA. However, the relatively high h2 values for mycelial growth at 35°C (0.63 ± 0.07) indicate that both populations BBT1 and OS6 of R. solani AG-1 IA have potential for adaptation to temperature stress.
Potencial adaptativo de populações de rhizoctonia solani AG-1 IA associadas ao arroz e à urochloa brizantha ao estresse térmico
Keywords: Environmental stress; Evolvability; Genetic variance; Thermal adaptation